2022
DOI: 10.1002/brb3.2511
|View full text |Cite
|
Sign up to set email alerts
|

Role of histidine decarboxylase gene in the pathogenesis of Tourette syndrome

Abstract: Tourette syndrome (TS) is caused by complex genetic and environmental factors and is characterized by tics. Histidine decarboxylase (HDC) mutation is a rare genetic cause with high penetrance in patients with TS. HDC-knockout (KO) mice have similar behavioral and neurochemical abnormalities as patients with TS. Therefore, HDC-KO mice are considered a valuable TS pathophysiological model as it reveals the underlying pathological mechanisms that cannot be obtained from patients with TS, thus advancing the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…In addition, an animal study showed that histidine decarboxylase knockout mice exhibited Tourette syn- drome-like phenomenology [28]. This indirectly supports the involvement of MAPK signaling pathway in Tourrete syndrome since histidine decarboxylase produces histamine, which in turn may be involved in regulating the physiological responses of cells by interacting with the MAPK signaling pathway [29].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, an animal study showed that histidine decarboxylase knockout mice exhibited Tourette syn- drome-like phenomenology [28]. This indirectly supports the involvement of MAPK signaling pathway in Tourrete syndrome since histidine decarboxylase produces histamine, which in turn may be involved in regulating the physiological responses of cells by interacting with the MAPK signaling pathway [29].…”
Section: Discussionmentioning
confidence: 80%
“…HDC homozygous and heterozygote null mice both developed Tourette-like syndrome, and an injection with histamine significantly reduced the stereotypies [ 15 ]. HDC KO mice appear similar to TS patients with the HDC Trp317Stop variant and also have increased levels of dopamine and elevated dopamine receptors in the substantia nigra [ 16 ]. In addition, mice lacking HDC show a reduced number of mast cells with less granules and altered morphology [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin is abundantly present in the digestive system and is closely related to the movement and secretion of the gastrointestinal tract, animal emotion regulation, learning, and memory [ 12 ]. HDC catalyzes histidine to histamine, which is involved in different physiological processes, including nerve signaling [ 13 ], cell proliferation [ 14 ], gastric acid secretion [ 15 , 16 ], and immune responses to allergies and inflammation [ 5 , 17 ]. CSAD catalyzes cysteine sulfinic acid to hypotaurine, which is further oxidized to taurine.…”
Section: Introductionmentioning
confidence: 99%